Evaluating the changes in molar incisor hypomineralization prevalence: A comparison of two cross‐sectional studies in two elementary schools in Mexico City between 2008 and 2017 - Maria Esther Irigoyen‐Camacho; Teresa Villanueva‐Gutierrez; Antonio Castano‐Seiquer; Nelly Molina‐Frechero; Marco Zepeda‐Zepeda; Leonor Sánchez‐Pérez (Wiley, 2020)
Abstract Background Little information is available on the trends over time of the prevalence of molar incisor hypomineralization (MIH). This condition may be preventing dental caries decline. Aim (a) To compare the prevalence of MIH, in Mexico City schoolchildren, evaluated in 2008 with a group evaluated in 2017, (b) to identify the association of MIH with dental caries, and (c) to assess the mother's perception of her child's oral health status. Design Two cross‐sectional studies performed in 2008 and in 2017 were compared. The oral examiner and the selected schools were the same in both surveys. Results A total of 549 schoolchildren were evaluated. The prevalence of MIH in the first survey was 20.3%, and 31.9 % in the second survey, (p = .002). Children with MIH were more likely to have dental caries. The odds ratio was 2.24 (p = .036) and 4.18 (p ˂ .001) in the first and second surveys, respectively. Mothers of children with MIH perceived worse oral health status of their children than the mothers whose children did not have MIH (odds ratio = 4.47, p ˂ .001). Conclusion The findings portray a clear increase in prevalence of MIH and highlight the need for increased awareness about this condition among dentists and the general population.